Mine infrastructure maintenance - Kumar, U.; Knights, P.; Kuruppu, Mahinda (Society for Mining, Metallurgy, and Exploration, Inc. (SME), 2011)
This Chapter is about maintenance of mine infrastructure so that a mine can safely and economically operate at or above design capacity without unscheduled stoppages or disturbances. Mine infrastructure refers to major capital installations at surface and undergrounds mine sites. Mine infrastructure is very site specific, being dependent on the mine location, size, mining method, equipment used and workforce. It includes access roads and declines, hoisting and ventilation shafts and equipment, drainage and pumping facilities, backfill preparation and delivery systems, power generation plant and distribution systems, workshops, service and warehouse facilities, offices, change house, chilled water plant, waste water management systems, construction facilities and other on-site infrastructure such as ore treatment plant and laboratories, communication networks and infrastructure for automation of mine operations. The primary objective of mine infrastructure maintenance is to ensure that production targets are met on time, safely and economically. Modern mining is mechanised and automated, requiring a high level of availability and reliability of mine infrastructure together with high level of maintenance preparedness to ensure that operations are maintained at designed (mine) capacity. The mine production system is critically dependent on the availability, reliability and capacity of mine infrastructure. The high level of system integration in modern mines has elevated the criticality of mine infrastructure. Furthermore, mechanised and automated mining systems are expected to safely perform at designed capacity around the clock, making access difficult for maintainers and complicating the task of maintenance scheduling. Because of the diversity of solutions to specific infrastructure requirements, this chapter does not intend to detail maintenance requirements for all types of infrastructure. Rather, it concentrates on general principals of infrastructure maintenance management, and provides some discussions on the following systems: • Hoisting systems• Underground roadways• Power generation and distribution systems• Mine dewatering systems• Maintenance workshop facilitiesThis Chapter presents some of the critical issues and challenges related to mine infrastructure maintenance.